SARCASTIC v2.0 - Vehicle datadomes - Michael Woollard; Hugh Griffiths; Matt Ritchie; David Blacknell (University College London, 2022)
This collection contains simulated compensated phase history data (CPHD) files generated using the SARCASTIC v2.0 software.
Keywords: 90905 Photogrammetry and Remote Sensing